2022
DOI: 10.1007/s11356-022-23207-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of injection temperature and formation slope on CO2 storage capacity and form in the Ordos Basin, China

Abstract: Carbon dioxide (CO2) storage capacity is the main criterion for assessing CO2 geological storage. Based on actual data from the Shiqianfeng formation in the Ordos Basin, three-dimensional (3D) models were built using the TOUGHVISUAL visualization software and simulated using the TOUGH2 integral finite difference modeling code with the ECO2N fluid property module to explore the impact of formation attributes (formation slope) and controllable factors (injection temperature) on CO2 storage capacity. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Based on the actual dip angle of the Shiqianfeng Formation (1–3°), the dip angle of the other simulation schemes was set to 3°. Based on previous experiences, , and the assurance that the injected CO 2 was in a supercritical state, three injection temperature values (31, 38, and 45 °C) were selected including isothermal and nonisothermal conditions. Considering the fracture pressure of the rock, the maximum safe injection pressure was 1.5 times the hydrostatic pressure (1.5P), ,, and three injection pressure values (1.3P, 1.4P, and 1.5P) were set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the actual dip angle of the Shiqianfeng Formation (1–3°), the dip angle of the other simulation schemes was set to 3°. Based on previous experiences, , and the assurance that the injected CO 2 was in a supercritical state, three injection temperature values (31, 38, and 45 °C) were selected including isothermal and nonisothermal conditions. Considering the fracture pressure of the rock, the maximum safe injection pressure was 1.5 times the hydrostatic pressure (1.5P), ,, and three injection pressure values (1.3P, 1.4P, and 1.5P) were set.…”
Section: Methodsmentioning
confidence: 99%
“…Greater reservoir depth leads to a higher stored CO 2 amount owing to the increase of pressure and temperature that induce higher density in storage . Many existing studies related to CO2 injections have been performed on the temperature and pressure distribution during CO2 injection. ,,,, Tawiah investigated the effect of temperature on CO 2 injectivity, and they found an inverse relationship between the bottomhole temperature of CO 2 and injectivity with the latter increasing. Ma found that an increase in injection temperature decreased the temperature gradient; injection pressure had a certain effect on the temperature gradient at low pressure, and the bottomhole pressure was effectively regulated by the injection pressure.…”
Section: Introductionmentioning
confidence: 99%